Ultrastructural observations on cellular and subcellular aspects of experimental Mycoplasma pneumoniae disease. - Carson, J L (1980)
The ultrastructural organization of Mycoplasma pneumoniae membranes and spatial relationships of this pathogen to epithelial cells in tracheal organ cultures were examined ultrastructurally by freeze-fracture techniques. Areas of morphologically distinct cell membrane variability characterized by membrane blebs and altered distributions of membrane associated particles were observed in replicas of M. pneumoniae cells. Inspection of the host tracheal epithelium demonstrated the alignment of M. pneumoniae to the epithelium with an accompanying deterioration in the integrity of the lumenal surface membranes and subsequent loss of the epithelial cell cytosol. Ciliary dysfunction was suggested by the observation of ciliary lesions and of disorganized epithelial cell cilia. The methodology used in these studies has permitted a new perspective of host-pathogen interactions at both the cellular and subcellular levels in tracheal organ cultures. These studies may also illustrate ultrastructural correlates of the alteration of host macromolecular synthesis in experimental M. pneumoniae infection.